The consolidation of learning groups in the continuing education project - Marinho da Silva, Fernanda Keila; Lousada Cracel, Viviane; Compiani, Maurício (Revista Diálogo Educacional, 2014)
This paper reports and discusses the importance and the consolidation of a study group composed by basic education teachers and academics in a collaborative proposal. Based on enunciated produced by teachers and records obtained from participation in collective meetings, this paper highlights the existence of reflexive advances of teachers and students’ difficulty to deal with barriers faced by teachers in their formative experience. This analysis is based on bakhtinian perspective on the enunciated, which involves social interaction as a way to understand the episodes cited in this paper. It concludes emphasizing the importance of consolidation of the group to the construction of reflective ways for academics and teacher and seeking a clarification of understanding of collaborative research.